Volunteering dynamics in leisure, tourism and hospitality: developing sustainable practices for well-being and social impact - Bertine Bargeman; Licia Calvi; Rodney Westerlaken; Geesje Duursma (Research in Hospitality Management, 2024)
This article explores the multifaceted landscape of volunteering in leisure, tourism and hospitality (LTH) organisations, acknowledging its fundamental role in civil society, and serves as the inception point for an in-depth research project. Volunteerism is explored in diverse forms, ranging from serious leisure engagements to episodic commitments, focusing on its transformative nature and impact on human capital. The study emphasises the integral role of volunteering as a strategic element in addressing human capital challenges and maintaining equilibrium between paid and unpaid staff. Ethical considerations, the significance of emotional intelligence and the potential of volunteering as a stepping stone to employment are emphasised. Differences in volunteering trends across LTH sectors are examined, and the need for a healthy environment balancing paid and unpaid staff is accentuated. The article introduces an integrated approach to studying volunteerism, employing qualitative narrative inquiry to understand the nuanced interactions among volunteers, organisations and their environments. The study aims to provide practical advice for LTH organisations, fostering a stable labour market where voluntary work is recognised as vital.